GEORGE PADMORE AND THE SOVIET MODEL OF THE BRITISH COMMONWEALTH. (August 2019) - WILLIAMS, THEO
Abstract : This article argues for an appreciation of the permeability of the Western socialist and black radical traditions and a recognition of their codevelopment. This relationship is illustrated through an analysis of George Padmore's intellectual history, particularly focusing on How Russia Transformed Her Colonial Empire (1946), in which Padmore applied Marxist ideas to his project of colonial liberation. The book functions as Padmore's manifesto for the transformation of the British Empire into a socialist federation following the model of the Soviet Union. Through comparisons with the manifestos of British socialist F. A. Ridley and American pan-Africanist W. E. B. Du Bois, this article contextualizes this manifesto within a moment of postwar internationalist optimism. This approach also facilitates a discussion of the meaning of "pan-Africanism" to Padmore, concluding that pan-Africanism was, for him, a methodology through which colonial liberation, and eventually world socialism, could be achieved.